COVID-19 Vaccine-associated Anaphylaxis and Allergic Reactions: Consensus Statements of the KAAACI Urticaria/Angioedema/Anaphylaxis Working Group - Kim, Mi-Ae (Allergy Asthma Immunol Res, 2021)
In the era of novel coronavirus epidemics, vaccines against coronavirus disease 2019 (COVID-19) have been recognized as the most effective public health interventions to control the pandemic. An adverse event following immunization (AEFI) is defined as any untoward occurrence following immunization, and the majority of AEFIs are caused by protective immune responses stimulated by vaccines. Most of the reported AEFIs are not serious, and many are not immunologically mediated or even reproducible on re-exposure. However, uncommon severe allergic adverse reactions, such as anaphylaxis or other allergic reactions, can occur after vaccinations. Confirmed allergic reactions to vaccines may be caused by residual non-human protein, preservatives, or stabilizers in the vaccine formulation (also known as excipients). There are 2 main potential allergenic/immunogenic excipients in COVID-19 vaccines, polyethylene glycol (PEG) and polysorbate 80. PEG, also known as macrogol, is an ingredient in various laxatives and injectable formulations, such as depot steroids. Polysorbate 80 is present in various medical products, creams, ointments, lotions, and medication tablets. Contraindications to the administration of COVID-19 vaccines include a previous history of severe allergic reactions to the first dose of COVID-19 vaccine or proven hypersensitivity to a vaccine component, such as PEG or polysorbate 80. Anaphylaxis or other allergic reactions following immunization can cause fear and loss of confidence in the safety of vaccines among the public. A better understanding of these events is thought to help alleviate concerns about the current COVID-19 vaccines and provide reassurance to the general population by analyzing the exact incidence of anaphylaxis and potential risk factors. COVID-19 vaccine-associated anaphylaxis could be prevented and managed by risk stratification based on our local and global experience.